Fractal Market Hypothesis and Markov Regime Switching Model: A Possible Synthesis and Integration - Doorasamy, Mishelle; Sarpong, Prince Kwasi (International Journal of Economics and Financial Issues, 2018)
Peters (1994) proposed the fractal market hypothesis (FMH) as an alternative to the efficient market hypothesis, following his criticism of the EMH. In this study, we analyse whether the fractal nature of a financial market determines its riskiness and degree of persistence as measured by its Hurst exponent. To do so, we utilize the Markov Switching Model to derive a persistence index (PI) to measure the level of persistence of selected indices on the Johannesburg Stock Exchange (JSE) and four other international stock markets. We conclude that markets with high Hurst exponents, show stronger persistence and less risk relative to markets with lower Hurst exponents. Keywords: Fractal Market Hypothesis, Markov Switching Model, Efficient Market Hypothesis JEL Classifications: G150, G140